Wayfinding Analysis for Evacuation Optimization with Urban Network Analysis in Disaster Preparedness School KB TK Masjid Syuhada - Setyawan, Siti Luzviminda Harum Pratiwi; Syafii, Nedyomukti Imam (Universitas Negeri Yogyakarta, 2024)
The existence of evacuation routes is one of the most important elements in disaster management because it will determine the smoothness of the rescue process during a disaster. An evacuation route is a route to an assembly point or exit that is assumed to be a safe space. Wayfinding is the process of moving from one point to another within the closest or fastest distance. In relation to the evacuation process, wayfinding will show the movement from a point, which in relation to buildings can be a specific space, to an exit or assembly point. As one of the disaster preparedness schools in Yogyakarta's Special Region, Masjid Syuhada Kindergarten was chosen as the site of the research. It is a complex of schools ranging from playgroup, kindergarten, elementary school, to junior high school, all of which are connected by the Syuhada Mosque. The analysis of evacuation routes in the kindergarten was conducted using Urban Network Analysis (UNA). UNA is used as a method to determine the effectiveness of providing evacuation routes in a building area because it can analyze trips between points, called origin and destination. Of the various analyses that UNA can perform, this research uses the closest facility analysis. In this study, the origins were all the class in the kindergarten which placed at the door as the open access and in the middle of the class if the class have two doors; while the destinations were the stairs which heading to assembly point. The conclusion is reached after analyzing the network that connects the origin of the class to the destination of the stairs, which is connected to the assembly point.